A NONOVARY‐SPECIFIC VITELLOGENIN RECEPTOR FROM THE ORIENTAL FRUIT FLY, Bactrocera dorsalis (HENDEL). Issue 4 (17th August 2015) - Lin, Wei‐Jen; Chien, Ching‐Yi; Tsai, Cheng‐Lung; Chen, Mei‐Er
ABSTRACT: The yolk protein precursor, vitellogenin (Vg), is absorbed into growing oocytes via receptor‐mediated endocytosis for embryonic development. In this study, a Vg receptor (VgR) cDNA of the oriental fruit fly ( Bactrocera dorsalis Hendel) was cloned via RT‐PCR and RACE (GenBank accession no. KR535603) and its expression analyzed. The BdVgR cDNA has a length of 6, 585 bp encoding 1, 923 amino acids. It has a conserved motif arrangement with other insect VgRs, and showed high identity to the B. cucurbitae VgR (91.4%). The expression of BdVgR mRNA and proteins was shown in both ovary and fat body. This is the first report on a nonovary‐specific VgR from a nonsocial insect. In ovary, the expression of BdVgR mRNA and proteins was inconsistent, with the transcription, but not protein, level high on D0. In fat body, the expression levels of BdVgR mRNA and proteins were high on days 5 and 6. The function of BdVgR in the fat body is not clear. However, it may be involved in reuptake of yolk proteins from the hemolymph as an amino acid reservoir or as autocrine regulation of yolk protein expression.